Agro-building clusters for solution critical challenges of sustainable development (2019)
The overarching purpose of the Sustainable Development Goals (SDGs) for the year 2030 is to end poverty, protect the planet and ensure prosperity for all. A major role in addressing these problems are the agricultural and construction sectors of the economy that provide basic human needs. However, at present, the agricultural sector not only provides food, but is one of the largest supplier of waste. Buildings and communal services are one of the most energy-intensive sectors of the world economy. A new sustainable development paradigm is based on the provisions of the circular economy. A circular economy is an economic system of closed loops in which raw materials, components and products lose their value as little as possible, renewable energy sources are used and systems thinking is at the core. In this article we will explain this definition in more detail. The organizational form of the creation of new formations can be agrarian and building clusters (ABCs). Cluster is completely self-sufficient that can power and feed itself with closed internal cycle of material and energy flows and the external supply of products and surplus energy to other consumers. ABC will use local organic (wood, straw, hemp) and inorganic (clay, soil, loam, sandy loam) materials for the construction of cheap Zero Energy Buildings (ZEB) or energy-positive homes, existing green technologies such as renewable energy sources, energy storage, organic food production, water management and waste-to-resource systems. In the frame of the presented study the autonomy of the building unit for ABS has been analyzed for the condition of Dnipro region, Ukraine.